Gender Differences in the Criminogenic Consequences Associated with Intergenerational Educational Mobility - Dennison, Christopher R. (American journal of criminal justice, 2019)
The present study examines gender differences in the relationship between intergenerational educational mobility and crime using data from The National Longitudinal Study of Adolescent to Adult Health. Drawing on recent trends in college completion among men and women, as well as theories of social control and general strain, it also examines whether these relationships are mediated by prosocial bonds (i.e., familial and employment status), economic stressors, and social-psychological measures in adulthood. Results suggest that upward mobility is associated with decreases in crime for both gender groups; however, downward mobility is associated with increases in crime only for women. Findings are discussed in the context of the relative importance of a college degree for men’s and women’s life chances.